Study of anatomy-diagnostic features of leaves of Cynara scolymus L. grown under the conditions of the Kyrgyz Republic - S. C. Chubakova; N. T. Farmanova; N. V. Bobkova; T. A. Mamatov (Разработка и регистрация лекарственных средств, 2025)
Introduction. Cynara scolymus shows potential benefits in various fields. Its nutritional value and health benefits make it a promising candidate for improving general well-being. C. scolymus exhibits anti-inflammatory, antioxidant, hepatoprotective, choleretic, antimicrobial and lipid-lowering neuroprotective properties. The large amount of polyphenol found in C. scolymus has antioxidant activity, which allows it to neutralize free radicals, preventing cell damage. This reduces the subsequent risk of developing conditions such as cancer, diabetes and cardiovascular disease. Therefore, this plant could potentially be developed as a candidate for new domestic pharmaceuticals. Plant characteristics including microscopic, physicochemical properties and phytochemical profiles are essential information to ensure the quality of raw materials in drug development.Alm. To study the macro and micromorphological characters of C. scolymus leaves for introduction into medical practice.Materials and methods. Dried leaves of artichoke (Cynara scolymus L.), collected in the flowering phase (June) of 2023, in the Osh region of the Kyrgyz Republic, were used as the object of the study. To detect characteristic external features of artichoke prickly leaves, an external examination of the analytical sample was carried out visually (10 × ). Microscopic and histochemical examination was carried out in accordance with GF RF XV ed. OFS 1.5.3.0003 "Microscopic and microchemical analysis of medicinal plant raw materials and drugs of plant origin" on a microscope Leica DM1000 (Leica Microsystems CMS GmbH, Germany) with an eyepiece 10×/20 and lenses 10×/0.25, 40×/0.65, 100×/1.25. The images were displayed through the program "Leica LAS v4.13 Software".Results and discussion. As a result of the research, characteristic morphological and anatomical features of artichoke leaves were established. Macroscopic features: leaves of oblong, broadly lanceolate shape, 50–70 cm long and 20–40 cm wide, unpaired, pinnately pinnately dissected, leaf margin coarsely ridged; petiole is fleshy, weakly expressed, ribbed; veining is pinnate. At the ends of leaf plates there are thin spike-like outgrowths. The color of the upper surface is grayish-green, the lower surface is silvery-gray or white-white. The odor when rubbed is weak, the taste of aqueous extract is sharply bitter. Microscopic features: upper epidermis consists of isodiametric and polygonal polygonal cells with straight walls, above veins epidermal cells are elongated. Stomata of the upper epidermis are oval, those of the lower epidermis are more rounded. Stomata are surrounded by 4–5 epidermal cells. Artichoke leaf trichomes are represented by simple and cephalic hairs. Simple hairs are multicellular, have a single row base consisting of 2–8 short, sometimes expanded cells. Simple setae end in a long, slender, sinuous thin-walled cell. Cephalic setae have a short multicellular bilobed pedicel and a rounded unicellular head, sometimes with a conspicuous yellowish oily content. The transverse section of the main vein (without leaf lamina) is semi-rounded with a slightly concave adaxial and convexly ribbed abaxial surface. Conductive bundles are collateral, large ones open and small ones closed. Simple and cephalic hairs can be observed on the epidermis of the vein.Conclusion. For the first time studies on macro- and microscopic features of leaves of prickly artichoke, grown in the conditions of the Kyrgyz Republic, necessary to establish the authenticity and quality assessment of raw materials have been carried out.